Identification of a High Affinity Nuclear Acceptor Site for Estrogen Receptor of Calf Uterus - Puca, Giovanni Alfredo (1974)
By means of affinity chromatography, specific nuclear acceptor sites for estradiol receptors are identified in a fraction that can be solubilized from purified nuclei with 2 M NaCl. Interaction between these acceptor sites and crude or partially purified estradiol receptor shows a high association constant (over 10(9) M). Receptor-acceptor interaction is dependent on physiological concentrations of 17β-estradiol; it is disrupted by high ionic strength. The nuclear acceptor sites appear to be protein in nature and exist in 5- to 10-fold excess over the estrogen binding sites present in the cytosol. Single- or double-stranded DNA does not bind estrogen-receptor complexes. Acceptor sites appear to be associated with basic nuclear proteins as judged by hydroxyapatite chromatography. The nuclear acceptor sites probably represent less than 0.1% of the purified basic proteins from the nucleus.